Perioperative outcome of thulium laser enucleation of the prostate versus robot-assisted simple prostatectomy: a propensity score-matched analysis: research article - Hartung, Friedrich; Kowalewski, Karl-Friedrich; Morina, Fehmi; Egen, Luisa; Neuberger, Manuel; Grüne, Britta; Wenk, Maren; Kriegmair, Maximilian; Nuhn, Philipp; Patroi, Paul; Westhoff, Niklas Christian; Honeck, Patrick; et al. (Urologia internationalis, 2023)
Introduction: The aim of this study was to investigate and compare clinical safety and efficiency of Thulium laser enucleation of the prostate (ThuLEP) and robot-assisted simple prostatectomy (RASP) for the treatment of large gland benign prostatic hyperplasia in a tertiary care center. Methods: Perioperative data of 39 patients who underwent RASP in our institution from 2015 to 2021 was collected. Propensity score matching using prostate volume, patient age, and body mass index (BMI) was performed from a database of 1,100 Patients treated by ThuLEP from 2009 to 2021. A total of 76 patients were matched. Preoperative parameters such as BMI, age, and prostate volume, as well as intra- and postoperative parameters such as operation time, resection weight, transfusion rate, postoperative catheterization time, length of hospital stay (LoS), hemoglobin drop, postoperative urinary retention (PUR), Clavien-Dindo Classification (CDC), and the Combined Complication Index (CCI), were evaluated. Results: There was no difference in mean hemoglobin drop (2.2 vs. 1.9 g/dL, p = 0.34), yet endoscopic surgery showed superiority in mean operation time (109 vs. 154 min, p < 0.001), mean postoperative catheterization time (3.3 vs. 7.2 days, p < 0.001), and mean LOS (5.4 vs. 8.4 days, p < 0.001). Complication rates evaluated by CDC (p = 0.11) and CCI (p = 0.89) were similar in both groups. Within the documented complications, transfusion rate (0 vs. 3, p = 0.08) and the occurrence of PUR (1 vs. 2, p = 0.5) showed no significant difference. Conclusion: ThuLEP and RASP show similar perioperative efficacy and a low rate of complications. ThuLEP had shorter operation times, shorter catheterization time, and a shorter LoS.